The Effectiveness of a Group Counseling Program Based ‎on Drama in Self-Esteem and Social Anxiety among ‎Female Adolescents - Tashtosh, Rami; Jdooa, Omaima (Jordan Journal of Educational Sciences, 2020)
This study aimed at exploring the effectiveness of a group counseling program based on drama in improving self-esteem and in reducing social anxiety among a sample of female adolescents. The sample of the study consisted of (30) eighth, ninth and tenth grade female students, who showed low self-esteem and high social anxiety. They were randomly divided into two equal groups: An experimental group and a control group. The experimental group undertook the counseling program, whereas the control group did not. To achieve the aims of the study, two scales: Heatherton and Polivy for self-esteem, for social anxiety Mattick and Clark were used. Meanwhile, the researchers designed a counseling program based on drama. Results revealed a statistical significant difference in the post-test of self-esteem and social anxiety in favor of the experimental group. In the same time, the study showed that means of social anxiety and self-esteem continued to improve positively in the follow up measurement, compared to the post-test, Thus, there are no statistical significant differences between post-test and follow up measurements. which reveal the effectiveness of the program for adolescents’ students This indicates female adolescents, retention of the effect of training, and as such demonstrating the stability of the program’s impact.